2019
DOI: 10.3390/ijms20184328
|View full text |Cite
|
Sign up to set email alerts
|

Differing Membrane Interactions of Two Highly Similar Drug-Metabolizing Cytochrome P450 Isoforms: CYP 2C9 and CYP 2C19

Abstract: The human cytochrome P450 (CYP) 2C9 and 2C19 enzymes are two highly similar isoforms with key roles in drug metabolism. They are anchored to the endoplasmic reticulum membrane by their N-terminal transmembrane helix and interactions of their cytoplasmic globular domain with the membrane. However, their crystal structures were determined after N-terminal truncation and mutating residues in the globular domain that contact the membrane. Therefore, the CYP-membrane interactions are not structurally well-character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
2
11
0
Order By: Relevance
“…For this, CYP3A4 was used as the test case for the insertion and orientation of a CYP enzyme in a POPC (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine) bilayer. We then extended the same approach to other major drug-metabolizing CYPs such as CYP2C9, CYP2C19, CYP1A1, CYP1A2, as well as to the human steroidogenic enzymes CYP17 and CYP19 that are [417][418][419]. From the results of our simulations, we have been able to identify differences in the orientations or the distance of the globular domain with respect to the membrane, and important residues at the membrane-protein interface that result in such differences.…”
Section: Drug Metabolizing Cytochrome P450 Enzymesmentioning
confidence: 96%
See 1 more Smart Citation
“…For this, CYP3A4 was used as the test case for the insertion and orientation of a CYP enzyme in a POPC (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine) bilayer. We then extended the same approach to other major drug-metabolizing CYPs such as CYP2C9, CYP2C19, CYP1A1, CYP1A2, as well as to the human steroidogenic enzymes CYP17 and CYP19 that are [417][418][419]. From the results of our simulations, we have been able to identify differences in the orientations or the distance of the globular domain with respect to the membrane, and important residues at the membrane-protein interface that result in such differences.…”
Section: Drug Metabolizing Cytochrome P450 Enzymesmentioning
confidence: 96%
“…Through our optimized multiscale simulation protocol, we identified that the two highly similar CYPs: CYP2C9 and CYP2C19 that share 94% sequence identity, can have not only distinct substrate specificities but also different membrane protein orientations and interactions [419]. Such differences were due to the primary sequence variation in the linker, beta-strand1, the B-C loop, helices F, F'-G', G regions and their turns.…”
Section: Drug Metabolizing Cytochrome P450 Enzymesmentioning
confidence: 99%
“…To date, there is no experimentally determined structure of a full CYP-CPR/cyt b5 complex available, although structures of the individual globular domains of the number of mammalian CYPs and CPRs have been determined by crystallography after removal of the N-terminal transmembrane domain to facilitate expression and crystallization 2 . Various modeling and simulation procedures have been developed to predict the orientation of full-length CYPs in phospholipid bilayers [16][17][18][19][20][21][22] . Notably, T. brucei CYP 51 simulated 20 prior to the determination in 2014 of the crystal structure of yeast CYP 51 23 , the only eukaryotic CYP for which a full-length structure has been determined experimentally, indicated a very similar orientation of the protein with respect to the membrane.…”
mentioning
confidence: 99%
“…The cytochrome P450 (CYP) superfamily consists of enzymes with highly diverse roles in the metabolism of drugs, fatty acids, steroids, and xenobiotics ( 1 , 2 ). Their genetic variants, single nucleotide polymorphisms (SNPs) in particular, can lead to therapy failure, severe toxicity, and increased susceptibility to cancer and other diseases caused by chemicals ( 3 ).…”
mentioning
confidence: 99%